2014
DOI: 10.1002/cctc.201402277
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Component Synthesis of β‐Enaminone and Pyrazole through Phosphine‐Free Palladium‐Catalyzed Cascade Carbonylation

Abstract: The carbonylative domino synthesis of enaminones and pyrazoles has been performed with the NN bidentate palladium catalyst to achieve excellent selectivity. These results have confirmed that the carbonylative Sonogashira coupling of iodobenzenes with terminal alkynes is accompanied by the Michael addition of amines or phenylhydrazine in a one‐pot method, which generates the desired products. This protocol demonstrates wide substrate tolerance, including hitherto unused aromatic amines, to yield the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 75 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Owing to their structural features, β-enaminones are frequently used as expedient N,O-bidentate ligands in organoboron complexes and transition-metal catalysis . In recent years, the β-enamine skeleton has been realized via the acid-catalyzed condensation of 1,3-diketones with amines, aza-Michael addition of amines to ynones, , aldol-type addition of carbonyl compounds to nitriles or activated isocyanides, and reductive ring opening of heterocycles . More recently, several radical coupling strategies were developed through decarboxylation coupling of α-keto acids and α-imine radicals. , However, the available methods are still arduous tasks due to the tedious multistep preparations, limited substrate scopes, and unavailability of starting materials or harsh reaction conditions.…”
mentioning
confidence: 99%
“…Owing to their structural features, β-enaminones are frequently used as expedient N,O-bidentate ligands in organoboron complexes and transition-metal catalysis . In recent years, the β-enamine skeleton has been realized via the acid-catalyzed condensation of 1,3-diketones with amines, aza-Michael addition of amines to ynones, , aldol-type addition of carbonyl compounds to nitriles or activated isocyanides, and reductive ring opening of heterocycles . More recently, several radical coupling strategies were developed through decarboxylation coupling of α-keto acids and α-imine radicals. , However, the available methods are still arduous tasks due to the tedious multistep preparations, limited substrate scopes, and unavailability of starting materials or harsh reaction conditions.…”
mentioning
confidence: 99%
“…A N−N bidentate palladium(II) complex 83 catalyzed four‐component domino reaction of aryl iodide 78 , phenylacetylene 79 , amine 80 and carbon monoxide 81 to prepare enaminones 82 was reported by Li and co‐workers (Scheme 14). [38] This method demonstrated broad substrate scope and good functional group tolerance. A cascade process of carbonylative Sonogashira coupling of iodobenzenes with terminal alkynes and Michael addition of an alkynone with an amine was proposed (Scheme 14).…”
Section: Multi‐component Reactionsmentioning
confidence: 96%
“…This heterogeneous palladium catalyst displayed high stability by showing no obvious leaching of palladium into the liquid phase or change in catalytic reactivity, no dispersion, and no size distribution after six runs. Subsequently, these authors reported the four component synthesis of β‐enaminones and pyrazoles from aryl iodide, arylacetylene, carbon monoxide, and amine with the same N,N‐bidentate palladium catalyst (Scheme b) . This N,N‐bidentate palladium catalyst exhibited good selectivity in the carbonylative Sonogashira reaction.…”
Section: Palladium‐catalyzed Cmcrsmentioning
confidence: 99%